Measurement of W±Z production cross sections and gauge boson polarisation in pp collisions at √s = 13 with the ATLAS detector - Aaboud, Morad; Anders, Christoph; Andrei, George Victor; Antel, Claire; Baas, Alessandra Edda; Bolz, Arthur; Brandt, Oleg; Djuvsland, Julia Isabell; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Geisler, Manuel Patrice; et al. (The European physical journal. C, Particles and fields, 2019)
This paper presents measurements of W±ZW±ZW^{± }Z production cross sections in pp collisions at a centre-of-mass energy of 13 TeVTeV\text {TeV}. The data were collected in 2015 and 2016 by the ATLAS experiment at the Large Hadron Collider, and correspond to an integrated luminosity of 36.1 fb−136.1 fb−136.1~\hbox {fb}^{-1}. The W±ZW±ZW^{± }Z candidate events are reconstructed using leptonic decay modes of the gauge bosons into electrons and muons. The measured inclusive cross section in the detector fiducial region for a single leptonic decay mode is σfid.W±Z→ℓ′νℓℓ=63.7± 1.0 (stat.)± 2.3 (syst.)± 1.4 (lumi.)σW±Z→ℓ′νℓℓfid.=63.7± 1.0 (stat.)± 2.3 (syst.)± 1.4 (lumi.)σ _{W^± Z → \ell ^{'} ν \ell \ell }^{\text {fid.}} = 63.7 \, ± ~1.0~\text {(stat.)} \, ± ~2.3~\text {(syst.)} \, ± ~1.4~\text {(lumi.)} fb, reproduced by the next-to-next-to-leading-order Standard Model prediction of 61.5+1.4−1.361.5−1.3+1.461.5^{+1.4}_{-1.3} fb. Cross sections for W+ZW+ZW^+Z and W−ZW−ZW^-Z production and their ratio are presented as well as differential cross sections for several kinematic observables. An analysis of angular distributions of leptons from decays of W and Z bosons is performed for the first time in pair-produced events in hadronic collisions, and integrated helicity fractions in the detector fiducial region are measured for the W and Z bosons separately. Of particular interest, the longitudinal helicity fraction of pair-produced vector bosons is also measured.